Impact of Non-Human Leukocyte Antigen-Specific Antibodies in Kidney and Heart Transplantation - Zhang, Xiaohai; Reinsmoen, Nancy L. (Frontiers in Immunology, 2017)
The presence of donor human leukocyte antigen (HLA) specific antibodies has been shown to be associated with graft loss and decreased patient survival, but it is not uncommon that donor specific HLA antibodies are absent in patients with biopsy proven antibody mediated rejection. In this review, we focus on the latest findings on antibodies against non-HLA antigens in kidney and heart transplantation. These non HLA antigens include myosin, vimentin, Kα1 tubulin, collagen and angiotensin II type I receptor (AT1R). It is suggested that the detrimental effects of HLA antibodies and non-HLA antibodies synergize together to impact graft outcome. Injury of graft by HLA antibodies can cause the exposure of neo-antigens which in turn stimulate the production of antibodies against non HLA antigens. On the other hand, the presence of non-HLA antibodies may increase the risk for a patient to develop HLA specific antibodies. These findings indicate it is imperative to stratify the patient’s immunologic risk by assessing both HLA and non-HLA antibodies.